Disposable and ultrasensitive label-free gold nanoparticle patterned poly(3,4-ethylenedioxythiophene-co-3-methylthiophene) electrode for electrochemical immunosensing of prostate-specific antigen - Uruc, Selen; Dokur, Ebrar; Gorduk, Ozge; Sahin, Yucel (ROYAL SOC CHEMISTRY, 2024)
This study introduces a novel label-free immunosensor that has the potential to be utilized for clinical screening and diagnosis of prostate cancer. The electrochemical immunosensor's performance was enhanced by combining 3,4-ethylenedioxythiophene (EDOT), 3-methylthiophene (3MT), and gold nanoparticles (AuNPs), enabling the accurate and sensitive determination of serum prostate specific antigen (PSA) concentrations. The immunosensor platform used [Fe(CN)(6)](3-/4-) as a redox probe to obtain the signal, and the DPV technique was used to correlate the signal with the PSA concentration. The linear range of AuNPs/p(EDOT-co-3MT)/PGE is 0.1 to 50 000 pg mL(-1), with a detection limit of 0.083 pg mL(-1). In interference studies with interferences such as bovine serum albumin, carcinoembryonic antigen, uric acid, ascorbic acid, vitamin B12, vitamin B9, l-tyrozine, l-phenylalanine, Cu2+, Fe2+, and Zn2+ the immunosensor showed excellent anti-interference properties. The designed sensor platform is facile, inexpensive, highly sensitive, and selective, and has a high surface area, excellent electrical conductivity, and biocompatibility. Furthermore, this technology is highly suitable for industrial-scale production and can be easily converted into point-of-care detection devices due to its low cost, reproducibility, selectivity, and accuracy.
Keywords: POLYANILINE; BIOSENSORS; Chemistry